1989
DOI: 10.3386/w3113
|View full text |Cite
|
Sign up to set email alerts
|

Social Security and the Determinants of Full and Partial Retirement: A Competing Risks Analysis

Abstract: Empirical analyses of retirement typically assume a single form of retirement. In this paper, I consider the determinants of retirement in a competing risks model which allows for full and partial retirement. Simulation results indicate that the large increase in Social Security benefits in the early 1970s has had moderate effects upon retirement, increasing the probability of early full retirement (before age 65) by less than ,5 percent and reducing the probability of partial retirement by 1-2 percent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Because Germany has very few part-time employees, we model only two states-fully in the labor force and fully retired-unlike the competing-risk analysis of Sueyoshi (1989). We use definition I for retired, based on the self-assessed labor force status (see section 5.4.3).…”
Section: Regression Resultsmentioning
confidence: 99%
“…Because Germany has very few part-time employees, we model only two states-fully in the labor force and fully retired-unlike the competing-risk analysis of Sueyoshi (1989). We use definition I for retired, based on the self-assessed labor force status (see section 5.4.3).…”
Section: Regression Resultsmentioning
confidence: 99%
“…reduced-form models, but to incorporate the accrual of SSW with a year of additional work; examples here include Fields and Mitchell (1984), Hausman and Wise (1985), and Sueyoshi (1989). Both of these types of studies continued to find an important, but modest, role for Social Security, and some (such as Fields and Mitchell) indicated a larger role for private pensions.…”
Section: B Previous Related Literaturementioning
confidence: 99%
“…Steinmeier (1984a, 2000) found estimates of the average duration in gradual retirement of 2.55 years in the HRS and 2.76 years in the older RHS data. In contrast, Sueyoshi (1989) estimated a much longer average duration using the RHS, using a different definition of gradual retirement. (Sueyoshi, 1989, Table 2) found that in the RHS, direct retirees left full employment at an average age of 64.8 years.…”
Section: Sequencesmentioning
confidence: 99%
“…Gustman and Steinmeier (1984b), Honig and Hanoch (1985) and Sueyoshi (1989) used RHS data for this analysis. Here, we focus on three studies that have used the more recent data from the HRS.…”
Section: Correlates Of Gradual Retirementmentioning
confidence: 99%